O JUSPOSITIVISMO EM BENTHAN, AUSTIN, KELSEN, ROSS E HART - Reis Friede (TRF2, 2018)
The debate involving the Jusnaturalism and the Juspositivism has been inspiring the reflections of jurists and philosophers. Although we can affirm that a great deal of the historical controversies associated to the confrontation between the Positive Law and the Natural Law have already been surpassed, there are still countless aspects which deserve an academic dedication. Notwithstanding dissonant opinions, which militate for the theoretical weakening of the subject, the passing of the centuries demonstrates exactly the opposite, given the non-elimination of the thinkers' esteem for the thematic now developed. Thus, the current article discourses about the theoretical contributions formulated by Bentham, Austin, Kelsen, Ross and Hart for the Legal Positivism.